KERJASAMA PEMANFAATAN AIR BERSIH ANTARA KABUPATEN SEMARANG DENGAN KOTA SEMARANG TAHUN 2013-2015 - Muhammad Faiz Ilham; Turtiantoro .; Muhammad Adnan (Journal of Politic and Government Studies, 2016)
Research on Water Utilization Cooperation between Semarang City and Semarang Regency Year 2013-2015 aims to understand the form of the clean water utilization cooperation done by both regions, as well as the realization of the cooperation in 2013-2015. Additionally, there will be explanation about the background of the cooperation, the motivating factors of the cooperation, and obstacles faced in the cooperation.This research uses descriptive qualitative method with data collection techniques such as interviews as the primary data and documents as secondary data. Informants in this study are the Semarang Regency Government and Semarang City’s regional water utility company.2Based on the research that has been done, it can be concluded that the cooperation in the utilization of clean water is the second time between Semarang Regency and Semarang City after previously conducted in 2004. The cooperation was established in 2013 and in a period of 25 years with the contribution of water. Realization of the cooperation in 2013-2015 did not achieve the targets agreed upon by the two regions. Inter-regional cooperation is not running optimally, there are still many things that need to be fixed in its management. But behind it all there is still good faith from both areas to solve existing problems.